Seasonal incidence of dengue and typhoid fever at the Philippine General Hospital from January 1995 to December 1997 - Tom, Allantonie (Animo Repository, 1999)
The purpose of this study is to associate climate to the incidence of dengue and typhoid fever in Philippine General Hospital from January 1995 to December 1997. Data regarding the number of dengue and typhoid fever cases was taken from Philippine General Hospital. Data regarding rainfall amount and temperature in the NCR was taken from PAGASA. Data showed that the incidence of dengue cases was higher during wet seasons as compared to dry seasons but does not have a direct relationship with seasonal changes. Study shows that an increase in rainfall amount will not always result to an increase in the number of dengue fever cases. The incidence of typhoid fever was found to be almost equal during wet and dry seasons. According to data gathered, the number of typhoid fever cases varied monthly regardless of rainfall amount.